Chirality Transfer in Gold(I)‐Catalysed Hydroalkoxylation of 1, 3‐Disubstituted Allenes. Issue 51 (11th November 2016) - Webster, Stacey; Sutherland, Daniel R.; Lee, Ai‐Lan
Abstract: Gold(I)‐catalysed intermolecular hydroalkoxylation of enantioenriched 1, 3‐disubstituted allenes was previously reported to occur with poor chirality transfer due to rapid allene racemisation. The first intermolecular hydroalkoxylation of allenes with efficient chirality transfer is reported here, exploiting conditions that suppress allene racemisation. A full substrate scope study reveals that excellent regio‐ and stereoselectivities are achieved when a σ‐withdrawing substituent is present. Abstract : Gold(I)‐catalyzed intermolecular hydroalkoxylation of enantioenriched 1, 3‐disubstituted allenes was previously reported to occur with poor chirality transfer due to rapid allene racemization. The first intermolecular hydroalkoxylation of allenes with efficient chirality transfer is reported, exploiting conditions that suppress allene racemization. Excellent regio‐ and stereoselectivities are achieved when a slightly σ‐withdrawing substituent is present.